Optical Sensor Implementation for Health Care Monitoring Based on Optical Fiber Technology: A Review - Nadia Ahmad Mohamad; Ali Al-Askery; Adnan Hussein Ali; Safiye Ghasemi Ghasemi (Journal of Techniques)
This study provides a review of the literature and an overview of optical fibers, as it is considered the highest class of intelligent materials, and there are many varieties and divisions based on the requirements of the manufacturer, it will review Optic Fiber Sensors (OFS) for measuring temperature and humidity. It has been divided into four main sections: The end user, and the environment. OFS Application in Healthcare, Impact OFS Qatar, Effect of chemical and mechanical properties of OFS Effect of external temperature changes in Surface Plasmon Resonance (SPR) for OFS Due to its unique characteristics, such as small size, lack of electromagnetic interference, high sensitivity, weights that allow sensing, accuracy, and very high dynamic range, it generates a fiber-optic sensor that is easy to manufacture and operate at the lowest possible cost. In addition, the development of Dispersive Sensor Systems (DSS) and OFS has found applications in both healthcare settings and strategies in biomedical research and structural Health Care Monitoring (HCM) to enhance the adoption of fiber-based medical equipment. Optics are two areas in which OFS has yet to realize its huge potential fully. The most recent published studies (2010-2023) were our main focus except for a few cases.